The Film Industry as a Sector of the Economy: Current Problems and Trends - A. B. Manakbayeva (Экономика: стратегия и практика, 2022)
Nowadays, the film industry is an important sector of the economy of many countries. Scientific interest in the research of cinema will grow with each passing day. This is because the film industry, consisting of producers and commercial organizations, is an object of investment and a successful asset. The article focuses on defining the role of the film industry in Kazakhstan’s economic and social development. The article’s primary goal is to identify and discuss current problems and trends in the development of the domestic film industry by analyzing its current state. The paper reveals the essence of the three main functions of the film industry - economic, social and ideological. The current state of the domestic film industry is analyzed by the use of statistical and sociological data. Relevant issues, socio-economic peculiarities, critical participants in the film market of Kazakhstan were considered. The research results established that private film companies dominate the domestic film business. The market is dominated byproducts of the foreign film industry, evidenced by their financial receipts. The task of increasing the share of domestic films, including national cinema in the film market, becomes more relevant. In addition, the article presents the problems that prevent the development of the domestic film industry and the factors that contribute to its further development. These factors include improving public administration in the field of cinematography, the establishment of clear parameters for the quality of domestic films, ensuring the principles of accessibility of Kazakhstani films.